Recovery Infectious Enterovirus 71 by Bac-to-Bac Expression System in vitro and in vivo - Lu, Baojing; Tang, Qi; Wang, Qianyun; Liu, Xuejuan; Peng, Hui; Zhu, Binbin; Xie, Li; Li, Zeng; Wang, Hanzhong; Zheng, Zhenhua; Wang, Linding; Li, Bao (Frontiers in Microbiology, 2022)
Enterovirus 71 (EV71) is one of the most important etiological agents for hand-foot-mouth disease (HFMD). Compared with coxsackievirus A16 (CA16) infection, EV71 infection is often associated with severe central nervous system (CNS) complications, such as encephalitis, encephalomyelitis, acute flaccid paralysis in infants and young children. In this study, we constructed a recombinant baculovirus with T7 ribonucleic acid polymerase under the control of a cytomegalovirus (CMV) promoter and simultaneously engineered the T7 promoter upstream of a full-length EV71 complementary deoxyribonucleic acid (cDNA) . After transduction into mammalian cells, typical cytopathic effects (CPEs) and VP1 signals were detected in cells transfected with recombinant baculovirus. Additionally, viral particles located in the cytoplasm of human rhabdomyosarcoma cells (Rd) and Vero cells were observed by electron microscop, indicating that EV71 was recovered using a Bac-to-Bac expression system in vitro. After four passages, the rescued virus had a growth curve and plaque morphology similar to those of parental. Furthermore, the Vp1 gene and the protein from the mouse brain were detected by reverse transcription polymerase chain reaction (RT-PCR) and immunohistochemistry after intracerebral injection of purified recombinant baculovirus. Typical CPEs were observed after inoculation of the supernatant from mouse brain to Rd cells, revealing a reconstruction of EV71 in vivo. Thus, we established a new approach to rescue EV71 based on a baculovirus expression system in vitro and in vivo, which may provide a safe and convenient platform for fundamental research and a strategy to rescue viruses that currently lack suitable cell culture and animal models.